Racial Equity: A case study in companies from Sinop/MT and its surroundings - Sandro dos Santos, Alex; Latuf Aguiar, Débora; Ferreira Silva, Elielson; Cristina Piovesan Cortezia , Mara; Guerrier, Sauveta (Seven Editora, 2023)
The movement of social responsibility and corporate governance, currently, is fraught with tensions, especially in the way in which companies have consolidated their actions in the vast field called “social”. In Brazil, it was only in the 1990s that sectors of the business community began to deal with the issue of valuing the diversity of the workforce more consistently. Given this reality, the importance of the Corporate Governance movement is evident, which consists of a system that works to optimize the performance of a company, that is, it is about directing, monitoring and encouraging companies, involving relationships in all parties, such as partners, investors, employees and creditors, facilitating access to capital. Within these principles, in this study, equity stands out, which is established in equivalence, in the fair treatment of all partners and stakeholders, and is in meeting the rights, duties, needs, interests and expectations of all interested parties. . The present research consists of an exploratory, descriptive study with a quali-quantitative approach in the form of a case study on the understanding of racial equity in companies in the city of Sinop and its surroundings. For the measurement, the answers of the interview questionnaire were identified, which obtained a “Yes” or “No” answer, each “Yes” corresponds to 1 point and the “No” corresponds to 0 point, each company being able to obtain a maximum of 13 points. . Therefore, concisely, small companies, which were part of this research, and with a few years of existence, have a tendency to be fickle about the understanding of equity. The vision of intending only to obtain profit makes a company weakened in its attributes and uniqueness. Its virtue is exposed to society when it shows itself diligent to human aspects. DOI: 10.56238/pacfdnsv1-106